Comparison of Mehlich-3 and DTPA Soil Tests for Analysis of Micronutrients in Kansas Soils - B. Rutter; D. A. Ruiz Diaz; L. Hargrave (Kansas Agricultural Experiment Station Research Reports, 2022)
Mehlich-3 (M3) was designed as a multi-nutrient soil test procedure and has become common at soil testing labs across the U.S. In Kansas, Mehlich-3 is predominately used as a soil test for phosphorus (P) and potassium (K), but recent studies have also investigated the use of M3 for the extraction of base cations and cation exchange capacity estimation. However, data relating M3 to traditional methods for soil micronutrient extraction remain scarce. The objective of this study was to investigate the relationship between M3 and diethylenetriamine pentaacetate (DTPA) extractable copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn) across a wide range of Kansas soils. Strong positive correlations were observed between M3 and DTPA for each metal (Fe, r = .91; Zn, r = .98; Cu, r = .92). Correlations between M3 and DTPA were positive but weak for Mn (r = 0.17). Regression analyses suggest these relationships were not one-to-one and were dependent on soil pH. Results from this study show that conversion of M3 to a “DTPA equivalent” is possible but should take soil pH into consideration, especially for Fe and Mn.
Keywords: zinc; copper; Mehlich-3; DTPA; soil testing; micronutrients; soil pH